Cardio-cerebrovascular diseases in Medellin - Colombia between 2000 and 2013: ¿a reference for public policy in health? - López-L, María Victoria; Pastor-D, María del Pilar; Arango-T, Gustavo Alberto; Restrepo-T, Yesica (Universidad y Salud, 2016)
Introduction: Public policy is a key element to government administration and its study is important when analyzing the impact it has on relevant issues evidenced in the epidemiological profile. Objective: To analyze the importance of cardio-cerebrovascular diseases in the development of public policy in health in Medellin between 2000 and 2013. Materials and methods: A qualitative approach with hermeneutic documentary analysis was done. The agreements approved by the Medellin council were taken as a base, from which those directly or indirectly related with these diseases were selected. Plans of action based on national and international policy guidelines were also reviewed. Results: An agreement that explicitly referred to these diseases was found. Most policy is oriented toward specific groups or issues related to health promotion and the prevention of cardio-cerebrovascular diseases. Follow-up and evaluation are the most overlooked stages of the public policy cycle. Conclusions: These results suggest the need for a broader definition of health that foments local policy development and impacts such a complex and important issue for the city by taking into account these diseases.